MODALITY, ETHOS AND STEREOTYPES IN WOMEN'S FINANCE ADVICE - Brunelli, Anna Flora [UNESP]; Verni, Rafaela De Paula [UNESP]; Gasparini-Bastos, Sandra Denise [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2019)
In this work, we analyze the ethos of a self-help book on finances directed specifically to the female audience, in order to reveal the image that the enunciator of the book projects of herself by its mode of enunciation. In addition, we analyze the images of women that this enunciator values and/or combat through their teachings, that is, we identify the stereotypes of women that this discourse collaborates to reinforce and/or transform. In order to operationalize the ethos research, we analyze the occurrences of the lexical expression of the modality, since modality is one of the forms of manifestation of subjectivity, more precisely a form through which the enunciator expresses his opinion or an attitude towards what says. Among the forms of lexical expression of the modality, we selected verbs (auxiliary and full), adjectives in predicative position and modal adverbs, and we rely on Functionalism as a specific theoretical-methodological apparatus of Linguistics as an auxiliary theory. The analysis reveals that an authoritarian tone prevails in the book, linked to the image of an assertive, convinced and focused enunciator in its goals, including guiding the reader in an assertive way. The analysis further reveals that the book reinforces the traditional gender stereotype according to which women are less prone to finances than men.
Keywords: self-help discourse; women; modality; ethos; stereotypes